EFFECT OF VARIOUS IRRIGANTS ON DENTAL BIOFILM: A REVIEW - S, Preetha; Raj, James D (Asian Journal of Pharmaceutical and Clinical Research, 2015)
ABSTRACT Objective: The objective of the article is to describe in brief the various endodontic irrigants on dental biofilm. Method: Articles based on various endodontic irrigants and dental biofilm were searched in an iterative manner from journals,books and sites such as PubMed. Result: It was found out that sodium hypochlorite is more effective on dental biofilms than chlorhexidine, MTAD, EDTA, herbal irrigants and new irrigants such as Qmix and tetraclean. Conclusion: Disinfection of root canal system is done using mechanical instrumentation,chemical irrigation along with medication.Sodium hypochlorite an excellent antibacterial agent,is the most commonly used and is more effective than other irrigants on dental biofilm. Keywords: Irrigants, Dental biofilm, Antimicrobial resistance, Sodium hypochlorite, Chlorhexidine, Tetraclean, Herbal irrigants.